Hepatitis E Virus Induces Brain Injury Probably Associated With Mitochondrial Apoptosis - Tian, Jijing; Shi, Ruihan; Xiao, Peng; Liu, Tianlong; She, Ruiping; Wu, Qiaoxing; An, Junqing; Hao, Wenzhuo; Soomro, MajidHussain (Frontiers in Cellular and Infection Microbiology, 2019)
Hepatitis E virus (HEV) infection has been associated with extrahepatic manifestations, particularly neurological disorders. Although it has been reported that HEV infection induced hepatocyte apoptosis associated with mitochondria injury, activation of mitochondrial apoptotic pathway in the central nervous system during HEV infection was not clearly understood. In this study, the induction of mitochondrial apoptosis-associated proteins and pro-inflammatory cytokines were detected in HEV infected Mongolian gerbil model and primary human brain microvascular endothelial cells (HBMVECs). Mitochondrial exhibited fragments with loss of cristae and matrix in HEV infected brain tissue by transmission electron microscope (TEM). In vitro studies showed that expression of NADPH oxidase 4 (NOX4) was significantly increased in HEV infected HBMVECs (p < 0.05), while ATP5A1 was significantly decreased (p < 0.01). Expressions of pro-apoptotic proteins were further evaluated. Bax was significantly increased in both HEV infected brain tissues and HBMVECs (p < 0.01). In vivo studies showed that caspase-9 and caspase-3 were activated after HEV inoculation (p < 0.01), associated with PCNA overexpression as response to apoptosis. Cytokines were measured to evaluate tissue inflammatory levels. Results showed that the release of TNFα and IL-1β were significantly increased after HEV infection (p < 0.01), which might be attributed to microglia activation characterized by high level of IBA1 expression (p < 0.01). Taken together, these data support that HEV infection induces high levels of pro-inflammatory cytokines, associated with mitochondria-mediated apoptosis. The results provide new insight into mechanisms of extra-hepatic injury of HEV infection, especially in the central nervous system.